GNAS mutations as prognostic biomarker in patients with relapsed peritoneal pseudomyxoma receiving metronomic capecitabine and bevacizumab: a clinical and translational study. Issue 1 (December 2016) - Pietrantonio, Filippo; Berenato, Rosa; Maggi, Claudia; Caporale, Marta; Milione, Massimo; Perrone, Federica; Tamborini, Elena; Baratti, Dario; Kusamura, Shigeki; Mariani, Luigi; Niger, Monica; Mennitto, Alessia; et al.
Abstract Background There is lack of evidence about systemic treatment of pseudomyxoma peritonei (PMP) relapsing after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. There is also lack of biomarkers able to predict outcomes beyond known clinical and pathological prognostic features. Methods Fifteen patients with relapsed PMP and progressive disease within the last 6 months were included and received metronomic capecitabine (625 mg/mq/day b.i.d.) and bevacizumab (7.5 mg/Kg three-weekly) until progressive disease/unacceptable toxicity. The primary endpoint was progression-free survival (PFS). Ion Torrent® next generation sequencing technology (Hot-spot Cancer Panel) was used to characterize molecular features. Results At a median follow up of 12 months, median PFS was 8.2 months and 1-year overall survival was 91 %. Partial responses were observed in 20 % of cases, but a significant reduction of tumor markers in up to 79 %. Treatment was very well tolerated without no new safety signals. All tumor samples except one hadKRAS mutations. Patients withGNAS mutations had a significantly shorter median PFS as compared toGNAS wild-type ones (5.3 months vs. not reached; p < 0.007). The results were externally validated on our previous series of PMP patients.GNAS mutations were rare in a parallel cohort of 121 advanced colorectal cancers (2.5 %), but were associated with peculiar clinical-pathological features and aggressive course. Conclusions Metronomic capecitabine and bevacizumab is an active and well tolerated option in patients with relapsed PMP. The negative prognostic effect ofGNAS mutations in gastrointestinal cancers warrants further confirmatory studies and may prompt the development of effective targeted strategies.